Lineamientos para la conservación Ex situ del guacamayo escarlata (Ara macao) en el distrito de Iquitos Perú 2020 - Rios Alava, Huber Augusto (2021)
The main objective of this research was, determine the guidelines scarlet macaw (Ara macao) ex situ conservation, it was made using a bibliographic review from books, papers, laws, and national and international official documents, interviews and polls to people who do ex situ conservation on Iquitos as well. The results of this research are the guideline for ex situ conservation, the main consideration for life cycle, diet, infrastructure and health for this specie, and for this it needs: a) a care program for the shedding cycles of the plumage; b) cages with suitable dimensions and locations; c) a balanced diet plan according to the development cycle and delivery schedules; d) a health control plan, for individuals of different ages of this specie to develop without problems.